The Relationship Between Bullying Behaviour and Self-Confidence in High School Adolescents - Padakokal, Florinda Marta; Ruliati, Luh Putu; Damayanti, Yeni; Lerik, Mariana Dinah Ch (Universitas Nusa Cendana, 2024)
The problem of bullying in educational institutions is a significant concern. In schools, peers can bully unaccepted individuals, which can diminish their self-confidence. This research examines the relationship between bullying and self-confidence among Wolwal State High School, Alor Regency adolescents. It is a quantitative correlational study using the Product Moment correlation test. The sample comprises 100 teenagers aged 13-19 from Wolwal village, selected through purposive sampling. Instruments include Radhiah's (2020) bullying behaviour scale, based on Coloroso's (2007) theory, and Cahyono's (2019) self-confidence scale, based on Lauster's (2012) theory. Data analysis reveals that physical, verbal, and relational bullying negatively correlates with self-confidence, indicating that increased bullying leads to lower self-confidence in high school students.